Barriers and facilitators to improving routine vaccination coverage in East Aceh during the COVID-19 pandemic: a qualitative study - Okfriani, Coraima; Martha, Evi (BKM Public Health and Community Medicine, 2023)
Purpose: East Aceh is one of the districts in Aceh Province that has a low rate of routine vaccination of children, especially in a pandemic situation. It is essential to research to understand more about the challenges in providing vaccination services due to COVID-19. Methods: This study used a qualitative approach with Rapid Assessment Procedure. Data was collected in three Puskesmas in East Aceh with the lowest vaccination coverage areas. The targeted participants in this study were: Caregivers, Health workers, Community cadres, Vaccine coordinators, and Vaccine advisors. Result: The phenomenon of COVID-19 vaccine refusal influenced caregivers’ to also refuse routine vaccination. Husband or father had a big role in determining whether children could get vaccinated. Caregivers were also afraid of vaccine side effects and vaccination methods using syringes as they often heard negative rumors about it. The lack of influential figure support also affected communities' perception of vaccination. On the other hand, several things might influence caregivers to bring their children to get vaccinated. Regular reminders from village midwives might influence caregivers to visit posyandu to get their children vaccinated. Good knowledge of the benefits of immunization for children is also important to raise caregivers’ awareness. Conclusion: This study recommends stakeholders and health professionals improve routine immunization programs, particularly in pandemic situations. The findings are anticipated to guide the creation of health campaign strategies encouraging caregivers to bring their children in for vaccinations.